THE ACTIVITY OF ESSENTIAL OILS OBTAINED FROM SPECIES AND INTERSPECIES HYBRIDS OF THE Mentha GENUS AGAINST SELECTED PLANT PATHOGENIC BACTERIA - Małgorzata Schollenberger; Tomasz M. Staniek; Elżbieta Paduch-Cichal; Beata Dasiewicz; Agnieszka Gadomska-Gajadhur; Ewa Mirzwa-Mróz (Acta Scientiarum Polonorum: Hortorum Cultus, 2018)
Plant essential oils of six aromatic herb species and interspecies hybrids of the family Lamiaceae – chocolate mint (Mentha piperita × ‘Chocolate’), pineapple mint (Mentha suaveolens ‘Variegata’), apple mint (Mentha × rotundifolia), spearmint (Mentha spicata), orange mint (Mentha × piperita ‘Granada’) and strawberry mint (Mentha × villosa ‘Strawberry’) – were investigated for antimicrobial effects against plant pathogenic bacteria: Agrobacterium tumefaciens, Pseudomonas syringae pv. syringae and Xanthomonas arboricola pv. corylina. The screening was carried out in vitro on agar plates filled with the target organism. All essential oils screened exhibited a higher level of antibacterial activity against A. tumefaciens and X. arboricola pv. corylina than streptomycin used as a standard in all tests. The antimicrobial effect of streptomycin and five mint oils was at the same level for P. syringae pv. syringae. There were no significant differences in the influence of the chocolate mint oil on the growth inhibition of all bacteria tested. Plant essential oils from pineapple mint, apple mint, spearmint and strawberry mint showed the weakest antimicrobial activity against P. syringae pv. syringae and the strongest towards A. tumefaciens and X. arboricola pv. corylina. The essential oils from strawberry mint, pineapple mint, spearmint and apple mint had the strongest effect on A. tumefaciens, and the lowest inhibitory activity was exhibited by the chocolate mint and orange mint essential oils. X. arboricola pv. corylina was the most sensitive to the strawberry mint, pineapple mint and spearmint oils. The chocolate mint oil showed the greatest activity against P. syringae pv. syringae.